Land Resource Cards: An Innovative Approach to Empower Farmers for Site-Specific Farm Resource Management - Ravi, K.N.; Patil, S.L.; Biswas, Hrittick; Ramesha, M.N.; Naik, B.S.; Ojasvi, P.R.; Duppal, Ravi; Naik, B.S.; Prabhavathi, M.; Kumar, Suresh; Morade, A.S. (Indian Journal of Extension Education, 2021)
The paper investigates an innovative extension approach of generation and distribution of Land Resource Cards, developed from Land Resource Inventory database, used for site-specific farm resource management in watersheds adopted under World Bank funded Sujala-III project. Extent of reach, satisfaction level and training status of Land Resource Cards in 12 model micro-watersheds located in different agro-climatic regions of Karnataka with a sample size of 720 farmers was assessed. The Land Resource Cards reached only 18% of farmers while 22% of farmers were trained for its utilization. However, 77% were satisfied with the information provided and 23% suggested for further improvement in cards for greater utility. The overall farmerâ€™s perception on capacity building on land resource cards revealed that they were very useful in farm-level resource management. Hence, need for replication of similar approach in all database driven watersheds to be implemented in the future with adoption of modifications is suggested.Â